The Production of Gelatin from Snapper Scales (Lutjanus camphecanus Sp.) through Enzymatic Pretreatment - Warlinda Eka Triastuti; Suprapto Suprapto; Elly Agustiani; Lailatul Qomariyah; Agung Subyakto; Treisnaning Widasgantri; Marchel Abednego Septa K (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Fish wastes such as fish bones and scales have a potential to be used as a gelatin source. It can be used as an alternative material to replace pork or bovine which ordinarily conflicted with religion issue. Gelatin from fish has different characteristics compared with mammalian source. It has several advantageous properties such as high amount of hydrophobic amino acids, less proline and hydroxy proline, lower gelling ability, and melting point. In this study, gelatin was produced from fish waste especially snapper scales using the bromelain enzyme at the pre-treatment stage to improve its characteristic. The snapper scales soaking in hot water at 80⁰C for about 30 minutes to remove the fat which attached the scales. A pre-treatment has been conducted using bromelain enzyme solution at various concentrations of 1%, 2%, 3%, 4% and 5% for 6 hours to remove non-collagenous proteins and loosen the bonds of the fish scales. The next step is demineralization using a 15% concentration of citric acid solution for 3 days. The ossein formed in the demineralization stage was then hydrolyzed at 50⁰C and 70⁰C for 9 hours with stirring at 300 rpm. The best gelatin yield was obtained from the pretreatment of bromelain enzyme solution with a concentration of 3% at a hydrolysis temperature of 70⁰C with a yield of 9.13%, pH value of 3.86, water content of 8%, ash content of 0.80%. FTIR spectra shows the presence of functional groups correspond to gelatin formation, such as carbon, hydrogen, hydroxyl group (O-H), carbonyl group (C=O), amine group (N-H) and alkene group (C=C). The heavy metal content test showed that the gelatin contained no heavy metal content of lead (Pb), mercury (Hg), cadmium (Cd) and arsenic (As).